Pengembangan Alat Evaluasi Pembelajaran Berbasis HOTS Menggunakan Website Wordwall pada Elemen Dasar Perbankan Kelas X Akuntansi di SMKS Yapalis Krian - Dyah Setyo Rini; Vivi Pratiwi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Learning under the National Curriculum with the Deep Learning approach requires contextual assessment instruments that are oriented toward Higher Order Thinking Skills (HOTS) to enhance students critical thinking abilities. This study aimed to develop a HOTS-based learning assessment instrument using the Wordwall website for the Basic Banking element at SMKS Yapalis Krian. The study employed a Research and Developmnet (R&D) method using the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The research participants included an assessment expert, a graphic design expert, and 35 grade Accounting students at SMKS Yapalis Krian. Data were collected through expert review sheets, validation sheets, student response questionnaires, and item analysis using the Anates software. The findings indicated that the Wordwall based learning assessment instrument obtained a feasibility score of 91% from the assessment expert and 100% from the graphic design expert, both categorized as highly feasible. Furthermore, students responses to the developed product reached 99%, which was classified as very positive. Therefore, the HOTS based learning assessment instrument developed using the Wordwall website for the Basic Banking element is considered highly feasible and received vert positive responses, indicating that it is suitable for use in learning assessment activities.